HEART Framework Evaluation of M-Paspor User Experience: Evaluasi UX Aplikasi M-Paspor dengan Metode HEART Framework - Novita Ramadayanti; Sumiati Sumiati (Academia Open, 2025)
General Background: In the era of digital transformation, the success of public service applications depends significantly on user experience (UX). Specific Background: The M-Paspor application by the Directorate General of Immigration Indonesia was developed to streamline passport services but suffers from low public ratings and recurring user complaints. Knowledge Gap: Despite its potential, comprehensive UX metrics that consider both functional and emotional dimensions have not systematically evaluated the application. Aims: This study aims to assess the usability of the M-Paspor application using the HEART Framework, which evaluates five key dimensions: Happiness, Engagement, Adoption, Retention, and Task Success. Results: From 100 user responses, the application scored high in Engagement (0.75), Retention (0.71), Happiness (0.66), and Adoption (0.64), but only medium in Task Success (0.57). Three dimensions did not meet the 70% usability target, revealing critical shortcomings in interface design, onboarding guidance, and payment or scheduling features. Novelty: This research applies the HEART Framework as a stand-alone evaluative tool to systematically diagnose user experience issues in a government mobile application. Implications: The findings offer actionable recommendations to improve M-Paspor’s usability and provide a replicable model for evaluating other public digital services. Highlights: 1. Engagement scored highest at 0.75 usability level. 2. Task Success dimension did not meet the target. 3. Design, guidance, and access features require improvement. Keywords: HEART Framework, M-Paspor, Usability, User Experience, Public Service App